Evidence based classification/staging system for Obstetric Fistula: Planning and preliminary intervention in Nigeria - Adeoye, S; OJengbede, OA; Efem, I; Amodu, A; Nasir, S; Wara, A; Amir, Y; Morhason-Bello, IO; Abdus-Salam, A; Bello, OO; Lawal, OO; Akinlusi, F; et al. (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To review the classification systems of obstetric fistula (OF). Methods: A two-day stakeholders’ meeting in Nigeria involving fistula surgeons, nurses, anesthetists, trainee, fistula desk officers at the federal and state government levels and other stakeholders was facilitated by Engender health. The meeting involved presentation of common classifications of obstetric fistula, critical analysis of each classification, group and plenary discussions. Presentation involved a critical analysis of classification parameters, strength and weakness. Three working groups designed classification criteria, prognostic scoring and suggested level of surgical skills needed to manage the patient. Outcome of each group work was presented and discussed in plenary. Each of the classification scenarios were modified by consensus and ratified at subsequent follow up meeting. Results: Three new classification systems of the OF were developed, and from these, a consensus classification was also developed in plenary. The initial three classifications developed from group work were similar to each other. Each classification considered size, location, previous repair, scaring, associated morbidity involvement of closing mechanism of the bladder neck, degree of urethral involvement and presence of transection of bladder neck (circumferential defect). The consensus classification, that was adopted, considered classification and prognostic scoring system. The four classification systems will be field tested to generate evidence for reliability and reproducibility. Conclusions: We believe a new classification system of obstetric fistula that will provide robust information to the managing team and patient is long overdue. This modest idea is a wake-up call for practitioners to design appropriate tool that is back up with reproducible evidence.